2015
DOI: 10.3109/14992027.2015.1005848
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of culture on hearing help-seeking and hearing-aid uptake

Abstract: This paper highlights the importance of psychological models and cross-cultural research in the area of hearing help-seeking and hearing-aid uptake, and consequently some directions for future research are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…We hypothesize that several aspects related to clients and their family (e.g., education, health literacy, and social, cultural, and ethnic background) and hearing healthcare professional attributes (i.e., health-care setting, education, and experience) may have influence on the communication behavior during clinical consultations. Hence, more research is needed from across the globe to better understand the phenomena that have been observed in the studies reported (Zhao et al, 2015). The qualitative and mixed methods design used in the studies reported have developed many hypotheses and shed light into an area of limited knowledge.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…We hypothesize that several aspects related to clients and their family (e.g., education, health literacy, and social, cultural, and ethnic background) and hearing healthcare professional attributes (i.e., health-care setting, education, and experience) may have influence on the communication behavior during clinical consultations. Hence, more research is needed from across the globe to better understand the phenomena that have been observed in the studies reported (Zhao et al, 2015). The qualitative and mixed methods design used in the studies reported have developed many hypotheses and shed light into an area of limited knowledge.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…In addition, there is a need to explore the relationship between different stages of change measures (Ingo et al, 2016) to assess the feasibility of single item measures (i.e., staging algorithm, Ida Institute-TL) especially for clinical purposes. Considering the studies using stages of change were performed in developed countries, it would be interesting and useful to conduct international and cross-culture studies (Zhao et al, 2015).…”
Section: Further Researchmentioning
confidence: 99%
“…In addition, cultural factors seemed to play a certain role in the respondents' social representations of hearing loss Manchaiah, Danermark, Vinay, et al, 2015). Hence, it is noteworthy that cultural values affect social representations in some way, because culture can be referred to as a broader network of representations held together by a whole community (Duveen, 2007;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%